Epidemiology of Chromosomal Syndromes in the State of Piauí: Report of the first 100 karyotype tests (Research, Society and Development, 2022)
Aims: Determine the epidemiological profile of the chromosomal syndromes of the first 100 patients who underwent the karyotype test at the Laboratory of Immunogenetics and Molecular Biology at the Federal University of Piauí (LIB-UFPI). Methods: This is an epidemiological and descriptive study, using secondary data based on medical records of the first 100 patients who underwent the karyotype exam at LIB-UFPI. Results: From 100 karyotype tests performed, 56% were male, 40% were female and 4% had undefined sex at the time of the test, age ranged from 0 to 49 years, with a predominance of patients up to 1 month of age 61% of the patients belonged to the city of Teresina and the others are distributed in another 25 municipalities of Piauí.The medical specialties that most requested the exam were pediatrics (48%) and neuropediatrics (23%), while only 8% of the requests were performed by geneticists, due to the scarcity of this specialty in the State. Among the chromosomal syndromes identified in the study are: Down Syndrome, Edward Syndrome, Patau Syndrome, Turner Syndrome, Klinefelter and mixed gonadal digenesis. Conclusion: The survey of epidemiological data on chromosomal syndromes in the State of Piauí is essential for understanding the distribution of rare diseases in the State and subsequent implementation of the PNAIPDR. In this context, the implementation and accreditation of the cytogenetics sector was fundamental for this survey and constituted the first step towards a future expansion of medical genetics in the State.